FACTORS OF FAILURE EXCLUSIVE BREASTFEEDING IN BENGKULU CITY - Pratiwi, Bintang Agustina; Yanuarti, Riska; Angraini, Wulan (Avicenna: Jurnal Ilmiah, 2020)
Bengkulu Province is in the fifth lowest position in achieving exclusive breastfeeding nationally. There was a decrease in the achievement of exclusive breastfeeding in Bengkulu Province by 6.7% from 2016-2017. The low achievement of exclusive breastfeeding will have an impact on the health status of babies and children in the future. This study aims to analyze the causes of failure of exclusive breastfeeding in the city of Bengkulu. This type of research is a quantitative method, the research was conducted at two health centers, namely the Betungan Health Center (Success) and the Community Health Center (Failure). The selection of puskesmas is based on data obtained from the Bengkulu City Health Office. The sample selection used purposive sampling, with a minimum sample size of 124 breastfeeding mothers. The data were analyzed by Univariate, Bivariate (Chi Square) and Multivariate (Multiple Logistic Regression). Mothers who do not provide exclusive breastfeeding are 79 (63.7%). There is a relationship between efforts to prepare exclusive breastfeeding, health worker support, advertisements for formula milk, support from husbands and support from mothers (parents) and exclusive breastfeeding in Bengkulu City. Advertising for formula milk is the most associated factor with exclusive breastfeeding. Information need for the nearest person and health care staff are not exposed to the mother’s milk formula ads.